BMI gain and dietary characteristics are risk factors of MASLD in non-obese individuals - Hirokazu Taniguchi; Miho Ueda; Yukiko Kobayashi; Takatomo Shima (Scientific Reports)
Abstract This longitudinal observational study aimed to evaluate whether cardiometabolic factors and dietary characteristics are determinants of metabolic dysfunction-associated steatotic liver disease (MASLD) in non-obese individuals (body mass index [BMI] < 25 kg/m²). The study was conducted at the Japanese Red Cross Society Kyoto Daiichi Hospital. Clinical data were longitudinally recorded at annual health checks. The diagnosis of MASLD was based on the results of abdominal ultrasonography and cardiometabolic criteria. Lifestyle behaviors and dietary characteristics were assessed using a self-administered questionnaire. A total of 4,100 non-obese middle-aged and older participants (1,636 men and 2,464 women) were followed up for an average of 6.44 ± 4.16 years. During the follow-up period, there were 410 new cases of MASLD in men (25.1%) and 484 in women (19.6%). The incidence rate was higher for men (39.7 per 1,000 person-years) than for women (30.1 per 1,000 person-years). Multivariable-adjusted logistic regression analyses using the rate of change per year with standardized values found that BMI gain was strongly associated with the onset of MASLD for both men (OR: 1.90, 95% CI: 1.64–2.19) and women (OR: 1.95, 95% CI: 1.72–2.21). Increased waist circumference and triglycerides were also associated with MASLD onset for both men and women. Lowering of high-density lipoprotein cholesterol was identified as a risk factor for MASLD in both men and women. Regarding dietary characteristics, the onset of MASLD was significantly and negatively associated with “often eating vegetables” for men (OR: 0.73, 95% CI: 0.57–0.93) and “often eating soy products” for women (OR: 0.71, 95% CI: 0.58–0.88), even after adjusting for BMI change and other covariates. These findings suggest that maintaining body weight and favorable dietary characteristics are key factors in the prevention of MASLD in non-obese individuals.